The anti-social network : cyberstalking victimization among college students - Reyns, Bradford W., 1979- (Criminal justice (LFB Scholarly Publishing LLC), 2012)
Cyberstalking is a disturbing reality for many in the United States and across the world. Yet, little is known about the extent or nature of cyberstalking victimization. Reyns?s intent is to estimate the extent of victimization, and by utilizing the lifestyle-routine activities perspective to identify risk factors for cyberstalking victimization among college students. Results indicate that certain online behaviors such as online social network usage, friending strangers online, engaging in online forms of deviance, and possessing a propensity toward low self-control increase one?s likelihood.